How do variations in dollar exchange rate impact food commodity prices in Africa? - David Umoru; Mishau Amedu (The Central European Review of Economics and Management (CEREM), 2022)
Aim: Commodity exporting nations have significant terms of trade swings, making their actual exchange rate unstable. This study looked at how variations in dollar exchange rate affected food commodity prices in Africa between 1990 and 2021. Design/Research methods: The study conducted GARCH analysis for ascertaining prevalence of volatilities of exchange rates and interest rates respectively in selected African countries. Also, we estimated both static and dynamic analysis driven by panel least squares and generalized method of moments (GMM) estimators on panel data from some commodity-exporting African, namely, Ghana, Gabon, Tunisia, Nigeria, and South Africa. Findings: The dynamic GMM results reveal exchange rate and interest rate variations taken together had positive effects on commodity prices. GARCH estimates demonstrate significant volatility growth using both normal and t multivariate distributions. However, based on empirical findings, t-distribution had largest maximized log-likelihood of -8920.1 and also had a satisfactory df of 26.82 (<30). The results demonstrate that the Nigerian Naira had highest coefficient of volatility of approximately 71.2%. This was followed by the Ghanaian Cedi with a negative volatility rate of 71% and the South African rand with a coefficient of 65%. However, while all countries had negative volatility with respect to interest rate, all countries except Ghana had positive volatility in exchange rate of their currency. Ghana, Gabon, Tunisia, and Nigeria showed negative exchange rate volatility. A possible explanation for this high volatilities in the aforementioned countries is persistent domestic inflation. Originality: The originality is rooted on establishment of food prices having some positive relation with pervasive exchange rate shocks. This is an indication of adverse effects of downward adjustment of exchange rate of local African currencies vis-à-vis the US dollar on food prices in the African countries covered in the study. Contributions: The contribution of the study lies on its explanation of the increase of food commodity prices due to variability calculated in terms of depreciation in dollar exchange rate. Empirically, it is a confirmation of a significant structural problem, exchange rate variation as a cause of domestic inflation in selected African countries. Limitations: Results have to be interpreted with care due to the small sample size. The results are rather a working hypothesis for future research.
Keywords: A20; F46; G20; 330; Interest rate variation; exchange rate variation; commodity export; food commodity prices; Africa